Reversal of Cognitive Impairment in gp120 Transgenic Mice by the Removal of the p75 Neurotrophin Receptor - Speidell, Andrew; Asuni, Gino Paolo; Avdoshina, Valeria; Scognamiglio, Serena; Forcelli, Patrick; Mocchetti, Italo (Frontiers in Cellular Neuroscience, 2019)
Activation of the p75 neurotrophin receptor (p75NTR), by the proneurotrophin brain-derived neurotrophic factor (proBDNF), triggers loss of synapses and promotes neuronal death. These pathological features are also caused by the human immunodeficiency virus-1 (HIV) envelope protein gp120, which increases the levels of proBDNF. To establish whether p75NTR plays a role in gp120-mediated neurite pruning, we exposed primary cultures of cortical neurons from p75NTR-/- mice to gp120. We found that the lack of p75NTR expression significantly reduced gp120-mediated neuronal cell death. To determine whether knocking down p75NTR is neuroprotective in vivo, we intercrossed gp120 transgenic (tg) mice with p75NTR heterozygous mice to obtain gp120tg mice lacking one or two p75NTR alleles. The removal of p75NTR alleles inhibited gp120-mediated decrease of excitatory synapses in the hippocampus, as measured by the levels of PSD95 and subunits of the N-methyl-D-Aspartate receptor in synaptosomes. Moreover, the deletion of only one copy of the p75NTR gene was sufficient to restore the cognitive impairment observed in gp120tg mice. Our data suggest that activation of p75NTR is one of the mechanisms crucial for the neurotoxic effect of gp120. These data indicate that p75NTR antagonists could provide an adjunct therapy against synaptic simplification caused by HIV.